Embedding Crowd-Vote as Knowledge Source to Support Decision Making on University Program Selection (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Crowd-vote has implemented as a part of a university program recommendation system, complementing the aspect of knowledge management.  The recommendation system is developed to support freshmen students’ decision making during program selection and uses for first time of enrolment.  The challenges of decision-making among students is formed by many influential factors like family, agents, universities and others.  Popular decision making models include rational, intuitive, among others. Rational models have series of sequential steps that involve a thinking process, while intuitive models are more on people experiences and recognition of the pattern based on what people believe and think how it will work.  Other models attempt to combine both rational and intuitive aspects of decision. The challenge is foreseen in capturing experts’ opinion as part of students’ decision making, since experts are the good source of knowledge to strengthen the process.  A prototype is developed for this purpose and constructive feedback from experts and students were collected to examine the significant use of crowd-vote using questionnaire survey. The objectives of this paper are to investigate the use of crowd-vote in leveraging decision making, and to evaluate the implementation of crowd-vote in supporting decision making during program selection.  The results from expert opinions and students’ evaluation are discussed.